(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The integration of Wave Energy Converters (WECs) into electrical grids remains a technical challenge due to the highly fluctuating nature of wave-induced power. Hybrid Energy Storage Systems (HESS), combining batteries and supercapacitors, offer a promising solution to mitigate power variability and ensure grid compliance. This study presents a modular approach for the preliminary design of HESS in WEC arrays, comparing centralised and decentralised storage configurations. A simplified wave-to-grid simulation model is employed, incorporating energy-maximising control strategies and a dual-filter power-smoothing scheme. Both control and storage systems are evaluated across multiple sea states and wave directions, providing a consistent comparison of sizing requirements. Results highlight that centralised layouts generally reduce total storage needs, particularly for supercapacitors, due to aggregation effects, though at the cost of reduced redundancy. The analysis underlines how resource variability and control strategy influence energy storage design and offers insights for the optimal deployment of WEC arrays with hybrid storage support.